Implementation of Artificial Intelligence and Robotics in Green Production for an Automotive Components Cluster in Chennai - Bhaskaran, E. (Productivity: A Quarterly Journal of The National Productivity Council, 2025)
This study explores the application of Artificial Intelligence (AI) and Robotics in promoting green production within an automotive component manufacturing cluster in Chennai. The objective of the study is to utilize these technologies to enhance both pro
Keywords: Automotive Components Cluster; Environmental Sustainability; Robotics in Green Production; Artificial Intelligence